2008
DOI: 10.1097/aln.0b013e31816d919b
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Basal Cholinergic Forebrain in the Mediation of General (Propofol) Anesthesia

Abstract: The anesthetic potency of propofol was increased in all rats with hippocampal lesions, whatever the injection sites, compared with controls. These results demonstrate that a cholinergic dysfunction in the basal forebrain potentiates the anesthetic effects of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
(39 reference statements)
1
43
0
1
Order By: Relevance
“…Sham-lesion rats received bilateral saline infusion (0.5 μl/side) into SI. The volume (0.5 μl) used was identical (Berntson et al, 2002;Kaur et al, 2008), or similar (0.4-0.8 μl used by Heckers et al, 1994;Laalou et al, 2008), to that used in other intra-NBM lesion studies. Saline with or without 192IgG-saporin was delivered by an infusion pump (Harvard Apparatus, South Natick, MA) over 10 min, after which the cannula was kept in place for another 10 min to allow for diffusion before retraction.…”
Section: Lesion Of Nbmmentioning
confidence: 99%
See 3 more Smart Citations
“…Sham-lesion rats received bilateral saline infusion (0.5 μl/side) into SI. The volume (0.5 μl) used was identical (Berntson et al, 2002;Kaur et al, 2008), or similar (0.4-0.8 μl used by Heckers et al, 1994;Laalou et al, 2008), to that used in other intra-NBM lesion studies. Saline with or without 192IgG-saporin was delivered by an infusion pump (Harvard Apparatus, South Natick, MA) over 10 min, after which the cannula was kept in place for another 10 min to allow for diffusion before retraction.…”
Section: Lesion Of Nbmmentioning
confidence: 99%
“…Increasing central Ach levels is known to reduce the depth of anesthesia (Meuret et al, 2000;Hudetz et al, 2003). Laalou et al (2008) reported that NBM lesion with 192IgG-saporin increased the anesthetic, but not the subanesthetic, effects of cumulative doses of propofol (i.p.). We showed that 5 mg/kg i.v.…”
Section: Correlation Of Averagementioning
confidence: 99%
See 2 more Smart Citations
“…Cholinergic neurotransmission plays an important role in the general anesthetic actions (8,9) and in the physiology of dreaming activity (10)(11)(12). Moreover, an enhanced central cholinergic neurotransmission is observed in the mental experience of dreaming during the REM sleep (11).…”
mentioning
confidence: 99%